Flame-retardant insulating powder coating for new energy automobile and preparation method of flame-retardant insulating powder coating

By adding modified flame retardant fillers, tougheners and composite curing agents to the flame retardant insulating powder coatings for new energy vehicles, the problem of cracks and holes in the curing process of powder coatings is solved, and the coating is high toughness, impact resistance and flame retardancy are achieved, which is suitable for the field of new energy vehicles.

CN119859456AActive Publication Date: 2025-04-22JIANGSU HUAGUANG POWDER +3

Patent Information

Application Number
CN202510344743.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

Existing powder coatings are prone to cracks and holes during the curing process, resulting in physical defects on the coating surface, limiting their use in high-demand applications such as new energy vehicles.

Method used

By adding modified flame retardant fillers, tougheners and composite curing agents to the flame retardant insulating powder coating for new energy vehicles, a stable cross-linking network is formed to improve the density and mechanical properties of the coating.

Benefits of technology

It has achieved the good toughness, impact resistance, flame retardant and self-repairing performance of flame retardant powder coatings for new energy vehicles, and is suitable for the high-demand new energy vehicles field.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flame-retardant insulating powder coating for a new energy automobile and a preparation method of the flame-retardant insulating powder coating, and belongs to the technical field of coatings. The flame-retardant insulating powder coating for the new energy automobile is prepared from the following raw material components in parts by mass: 380 to 384 parts of epoxy resin, 56 to 58 parts of a toughening agent, 5 to 10 parts of modified flame-retardant filler, 100 to 101 parts of a composite curing agent, 5 parts of a flatting agent, 1 part of benzoin and 0.7 part of an accelerant, the toughening agent is obtained by carrying out a reaction on an isophorone diisocyanate tripolymer, 4-bromophenol and N-p-coumaroyl tyramine; the modified flame-retardant filler is obtained by firstly wrapping hexagonal boron nitride with polydopamine and then modifying with a silane coupling agent; the silane coupling agent is obtained by combining 4-benzonitrile oxygen butyl trimethoxy silane and a sulfydryl silane coupling agent; and the composite curing agent is obtained by combining 4, 4-diaminodiphenylmethane and amino-sulfydryl functional organic polysiloxane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flame retardant insulating powder coating for new energy vehicles and a preparation method thereof. Background Art

[0002] As global awareness of environmental protection increases, the release of volatile organic compounds (VOCs) has become an environmental issue of widespread concern. In this context, powder coatings, as an environmentally friendly coating, are favored because they do not release volatile organic compounds during use. Powder coatings are a 100% solid powder coating composed of resins, curing agents, and various pigment fillers that are melt-mixed. They are often used as surface coatings and decorative materials and are widely used in construction, industry, automobiles, home appliances and other fields. Compared with traditional solvent and liquid coatings, powder coatings not only meet the "4E" principles of contemporary environmental protection (environmental protection, high efficiency, ecology, and economy), but their use is also increasing year by year.

[0003] In order to meet the market demand for high-performance coatings, the research and development of powder coatings is moving towards improving their physical properties. Despite this, most of the current research on the functionalization of coatings is focused on liquid coatings, and there is relatively little research on powder coatings, especially flame-retardant insulating powder coatings for new energy vehicles. Epoxy resin has become one of the widely used resins in powder coatings due to its good corrosion resistance, high mechanical strength and excellent insulation. However, due to the influence of the high-density three-dimensional cross-linked network formed by epoxy resin during the curing process, cracks and holes will inevitably appear, resulting in physical defects on the coating surface. These problems limit the use of powder coatings in more demanding applications, such as coatings with good toughness, impact resistance, flame retardancy and thermal conductivity required in the field of new energy vehicles.

[0004] Therefore, the applicant prepared a flame retardant insulating powder coating for new energy vehicles. Summary of the invention

[0005] The purpose of the present invention is to provide a flame retardant insulating powder coating for new energy vehicles and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.

[0006] The technical solution for achieving the purpose of the present invention is:

[0007] The first aspect of the present invention provides a flame retardant insulating powder coating for new energy vehicles. The raw material components include, by weight: 380-384 parts by weight of epoxy resin, 56-58 parts by weight of toughening agent, 5-10 parts by weight of modified flame retardant filler, 100-101 parts by weight of composite curing agent, 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator.

[0008] Furthermore, the toughening agent is obtained by reacting isophorone diisocyanate trimer, 4-bromophenol and N-p-coumaroyltyramine.

[0009] Furthermore, the modified flame retardant filler is obtained by first wrapping hexagonal boron nitride with polydopamine and then modifying it with a silane coupling agent.

[0010] Furthermore, the silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and a mercaptosilane coupling agent.

[0011] Furthermore, the composite curing agent includes 4,4-diaminodiphenylmethane and amino-mercapto-functional organopolysiloxane.

[0012] The second aspect of the present invention provides a method for preparing the flame-retardant insulating powder coating for new energy vehicles as described in the first aspect, the preparation steps comprising:

[0013] (1) Slowly add 5 parts by mass of toughening agent and 0.24 to 0.26 parts by mass of iodine to 5.6 to 5.8 parts by mass of magnesium powder and 50 to 60 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 101 to 123 parts by mass of a mixture of toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 2.5 to 3.5 hours, wherein the mass of toughening agent in the mixture of toughening agent and ether is 51 to 53 parts by mass, and the mass of ether is 50 to 70 parts by mass. After cooling to room temperature, add 45-70 parts by mass of ether dispersion of modified flame retardant filler, add within 60 minutes, reflux for 4.5-5.5 hours and then cool to room temperature, wherein the mass of modified flame retardant filler in the ether dispersion of modified flame retardant filler is 5-10 parts by mass, and the mass of ether is 40-60 parts by mass; then add 40-60 parts by mass of methanol, stir at room temperature for 50-70 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0014] (2) 100-101 parts by weight of the composite curing agent and 36% hydrochloric acid solution are mixed in a mass ratio of 1:1.8-2.2, followed by filtration and drying, followed by adding 5-15 times the mass of the composite curing agent into dichloromethane and stirring for 30-60 minutes, followed by adding the premix obtained in step (1) and continuing to stir and react for 2-4 hours, and removing dichloromethane by rotary evaporation at 40-50° C. to obtain a secondary mixture;

[0015] (3) 380-384 parts by weight of epoxy resin, the secondary mixture obtained in step (2), 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator were manually mixed and then extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles.

[0016] Furthermore, the preparation steps of the toughening agent are as follows: 16.4-16.44 parts by mass of N-p-coumaryltyramine are dissolved in 70-74 parts by mass of 1,4-dioxane, and then 11-11.2 parts by mass of isophorone diisocyanate trimer is added at 1-3s / drop, the temperature is raised to 78-82°C and stirred for reaction for 3.5-4.5h, and then 77.8-81.9 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.8-7.9 parts by mass of 4-bromophenol is dissolved in 70-74 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 3.5-4.5h. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 68-72°C to obtain a toughening agent.

[0017] Furthermore, the preparation steps of the modified flame retardant filler are as follows: 2.2-2.6 parts by mass of dopamine hydrochloride and 5-7 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L, pH 8.5 tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, ultrasonically treated for 25-35 minutes, stirred at room temperature for reaction for 23-25 ​​hours, vacuum filtered after the reaction, washed the precipitate with deionized water until the filtrate was colorless, and then dried at 60°C for 23-25 ​​hours to obtain polydopamine-wrapped hexagonal boron nitride; 9-11 parts by weight of hexagonal boron nitride wrapped with polydopamine were added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.4-0.6 parts by weight of a silane coupling agent were added, ultrasonicated for 15-25 minutes, stirred at 500 rpm for 5.5-6.5 hours at 78-82°C, and then centrifuged at 6000 rpm for 10 minutes, washed with ethanol for multiple times, and vacuum dried at 60°C for 23-25 ​​hours to obtain a modified flame retardant filler.

[0018] Furthermore, the silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:0.8-1.2; wherein the mercaptosilane coupling agent is preferably silane coupling agent KH580.

[0019] Furthermore, the composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto-functional organic polysiloxane in a mass ratio of 1:0.4-0.6.

[0020] By adopting the above technical solution, the present invention has the following beneficial effects:

[0021] (1) The flame retardant insulating powder coating for new energy vehicles of the present invention comprises, by weight, 380-384 parts by weight of epoxy resin, 56-58 parts by weight of toughening agent, 5-10 parts by weight of modified flame retardant filler, 100-101 parts by weight of composite curing agent, 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator; by adding modified flame retardant filler, toughening agent, and composite curing agent to the flame retardant insulating powder coating for new energy vehicles, the flame retardant insulating powder coating for new energy vehicles has good toughness, impact resistance, and flame retardancy.

[0022] (2) The present invention adds a modified flame retardant filler to the flame retardant insulating powder coating for new energy vehicles, wherein the modified flame retardant filler is obtained by first wrapping hexagonal boron nitride with polydopamine and then modifying it with a silane coupling agent; the silane coupling agent is obtained by combining 4-benzonitrile oxybutyltrimethoxysilane and mercaptosilane coupling agent; hexagonal boron nitride exhibits excellent properties in thermal conductivity, electrical insulation, anti-oxidation and radiation shielding. Hexagonal boron nitride can not only fill the microcracks caused by resin curing to improve the density of the coating, but also its layered structure can form a "maze" in the coating. The "lip-lip effect" prolongs the penetration path of corrosive media or combustion gases, giving the coating flame retardant and anti-corrosion properties; however, the interaction force between B atoms and N atoms in adjacent layers is called lip-lip interaction, which causes hexagonal boron nitride to easily agglomerate and has poor dispersion in the coating, greatly reducing the apparent properties and mechanical properties of the coating; the modified flame retardant filler obtained by first wrapping hexagonal boron nitride with polydopamine and then modifying it with a silane coupling agent can effectively improve the dispersibility and interfacial compatibility of hexagonal boron nitride in the coating, thereby ensuring and improving the apparent properties and mechanical properties of the coating.

[0023] (3) The toughening agent of the present invention is obtained by reacting isophorone diisocyanate trimer, 4-bromophenol and N-p-coumaryltyramide; the hydrogen bonds in the molecular structure of the toughening agent serve as sacrificial bonds to increase the toughness of the resin, while the high rigidity structures of the benzene ring and the six-membered ring and the rigid conjugated structure of the benzene ring olefin enhance the mechanical properties to a certain extent; and the rigid conjugated structure of the benzene ring olefin in the molecular structure of the toughening agent promotes the formation of residual carbon and gives the material higher thermal stability; in addition, the toughening agent introduces nitrogen-containing structures and rigid conjugated structures into the epoxy resin matrix, which can, on the one hand, produce non-flammable gases through thermal decomposition, reduce toxic and harmful smoke, and significantly improve its fire safety; on the other hand, the toughening agent reacts with other raw material components in the powder coating to form a stable cross-linked network, and after combustion, forms a dense carbon layer, which serves as a protective layer for the resin matrix and can effectively prevent further combustion of the resin matrix, thereby enhancing the flame retardant properties of the flame-retardant insulating powder coating for new energy vehicles.

[0024] (4) The composite curing agent of the present invention is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto-functional organopolysiloxane; wherein, the introduction of amino-mercapto-functional organopolysiloxane as an epoxy resin curing agent introduces a flexible organosilicon molecular chain into the coating, which effectively improves the toughness of the epoxy resin cured material as a second phase containing a flexible structure; and during the combustion process, the amino-mercapto-functional organopolysiloxane is heated to self-crosslink to form a continuous and dense silica layer, which prevents the substrate from igniting and burning, thereby reducing the heat loss inside the polymer, and the hexagonal boron nitride in the modified flame retardant filler in the coating forms a physical barrier to heat and volatile gases in a condensed state, namely the so-called "tortuous path" effect, which can synergize with the amino-mercapto-functional organopolysiloxane to provide a good barrier, limit the transmission of external heat and flammable gases, and slow down the diffusion of volatile combustibles, further enhancing the flame retardant properties of the flame retardant insulating powder coating for new energy vehicles.

[0025] (5) The present invention first premixes a toughening agent and a modified flame retardant filler to obtain a premix, then mixes the premix with a composite curing agent, and finally melts, mixes, and extrude with epoxy resin, a leveling agent, benzoin, and an accelerator to obtain a flame retardant insulating powder coating for new energy vehicles. The bromobenzene on the toughening agent reacts with the benzonitrile on the modified flame retardant filler to form a diphenyl ketone imine derivative, and then the premix is ​​mixed with the composite curing agent. The diphenyl imine in the premix reacts with the primary amine to block and protect the primary amine, which can effectively slow down the curing speed and avoid the excessive curing speed causing a large number of pinholes to appear when the coating is used for thick coating, i.e., the film thickness is ≥90 μm, thereby affecting the coating surface performance. At the same time, the thiol in the premix reacts with the thiol in the composite curing agent to cross-link to form a dynamic disulfide bond, which gives the flame retardant insulating powder coating for new energy vehicles better self-healing performance. DETAILED DESCRIPTION

[0026] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0027] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0028] Some of the raw materials of the embodiments of the present invention and the comparative examples are as follows:

[0029] Mercaptosilane coupling agent: Silane coupling agent KH580.

[0030] The epoxy resin used is E51 epoxy resin, which has an average epoxy value of 0.51 and an average hydroxyl value of 0.046.

[0031] The leveling agent used is leveling agent GLP588.

[0032] The accelerator used is 2-methylimidazole.

[0033] The preparation steps of 4-benzonitrileoxybutyltrimethoxysilane are as follows: 4-hydroxybenzonitrile, potassium hydroxide and tetrahydrofuran are added into a wide-mouth bottle with a capacity of 1 L, and 4-bromo-1-butene is added after the temperature is reduced to 20°C, wherein the molar ratio of 4-hydroxybenzonitrile, 4-bromo-1-butene and potassium hydroxide is 1:2:3, and the mass ratio of 4-hydroxybenzonitrile and tetrahydrofuran is 25:555, and the mixture is stirred at room temperature overnight, tetrahydrofuran and excess 4-bromo-1-butene are removed by rotation, and then dichloromethane is added, and the organic phase is extracted with deionized water and saturated brine in sequence, and the organic phase is dried with anhydrous sodium sulfate, and most of the solvent is removed by a rotary evaporator, and the residue is mixed with a sample, and finally The method is purified by column chromatography using ethyl acetate / petroleum ether = 3% to obtain 4-(allylbutyloxy)benzonitrile; 4-(allylbutyloxy)benzonitrile, trimethoxysilane, catalyst chloroplatinic acid and 1,4-dioxane are sequentially added to a single-mouth bottle, wherein the molar ratio of 4-(allylbutyloxy)benzonitrile, trimethoxysilane and catalyst chloroplatinic acid is 1:2:0.04, and the mass ratio of 4-(allylbutyloxy)benzonitrile to 1,4-dioxane is 10:258; the reaction solution is stirred at 115° C. overnight under nitrogen protection, the reaction solution is cooled to room temperature, and then the sample is dried by a rotary evaporator, and finally purified by column chromatography using ethyl acetate / petroleum ether = 3% to obtain 4-benzonitrileoxybutyltrimethoxysilane.

[0034] The preparation steps of amino-mercapto functional organic polysiloxane are as follows: 31.5 parts by mass of silanol-terminated polydimethylsiloxane Tech-2170 produced by Shanghai Tiger Polymer Technology Co., Ltd. are added to a reaction container, followed by adding 4.9 parts by mass of aminopropylmethyldimethoxysilane and 4.1 parts by mass of mercaptopropylmethyldiethoxysilane, and then adding 0.7 parts by mass of barium hydroxide and 0.26 parts by mass of sodium orthophosphate, followed by heating to 80°C and keeping warm for 3 hours, then pressing to 200 mbar and leaving for 1 to 3 hours, then adding 10.1 parts by mass of straight-chain aliphatic tridecanol and maintaining the reaction at 80°C and atmospheric pressure for 2 hours to obtain amino-mercapto functional organic polysiloxane.

[0035] (Example 1)

[0036] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0037] (1) Slowly add 5 parts by mass of a toughening agent and 0.24 parts by mass of iodine to 5.6 parts by mass of magnesium powder and 50 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, dropwise add 101 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, complete the dropwise addition within 60 minutes, and then reflux for 2.5 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 51 parts by mass, and the mass of the ether is 50 parts by mass; after cooling to room temperature, add 45 parts by mass of an ether dispersion of a modified flame retardant filler, complete the addition within 60 minutes, reflux for reaction for 4.5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 5 parts by mass, and the mass of the ether is 40 parts by mass; then add 40 parts by mass of methanol, stir at room temperature for 50 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0038] (2) 100 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:1.8, followed by filtration and drying, and then added to dichloromethane 5 times the mass of the composite curing agent and stirred for 30 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 2 hours, and the dichloromethane was removed by rotary evaporation at 40° C. to obtain a secondary mixture;

[0039] (3) 380 parts by weight of epoxy resin, the secondary mixture obtained in step (2), 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0040] The preparation steps of the toughening agent are as follows: 16.4 parts by mass of N-p-coumaryltyramine are dissolved in 70 parts by mass of 1,4-dioxane, and then 11 parts by mass of isophorone diisocyanate trimer is added at 1s / drop, the temperature is raised to 78°C and stirred for reaction for 3.5h, and then 77.8 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.8 parts by mass of 4-bromophenol is dissolved in 70 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 3.5h. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 68°C to obtain a toughening agent.

[0041] The preparation steps of the modified flame retardant filler are as follows: 2.2 parts by mass of dopamine hydrochloride and 5 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 25 minutes, the mixture is stirred at room temperature for reaction for 23 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 23 hours to obtain hexagonal boron nitride wrapped with polydopamine; 9 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.4 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 15 minutes, stirring is performed at 500 rpm at 78°C for 5.5 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed 3 times with ethanol, and vacuum drying is performed at 60°C for 23 hours to obtain a modified flame retardant filler.

[0042] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:0.8.

[0043] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.4.

[0044] (Example 2)

[0045] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0046] (1) Slowly add 5 parts by mass of a toughening agent and 0.25 parts by mass of iodine to 5.7 parts by mass of magnesium powder and 55 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 112 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 52 parts by mass, and the mass of the ether is 60 parts by mass; after cooling to room temperature, add 57.5 parts by mass of an ether dispersion of a modified flame retardant filler, and complete the addition within 60 minutes, reflux for reaction for 5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 7.5 parts by mass, and the mass of the ether is 50 parts by mass; then add 50 parts by mass of methanol and stir at room temperature for 60 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0047] (2) 100.5 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2, followed by filtration and drying, and then added to dichloromethane (10 times the mass of the composite curing agent) and stirred for 45 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 3 hours, and the dichloromethane was removed by rotary evaporation at 45° C. to obtain a secondary mixture;

[0048] (3) 382 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0049] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0050] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0051] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:1.

[0052] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0053] (Example 3)

[0054] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0055] (1) Slowly add 5 parts by mass of a toughening agent and 0.26 parts by mass of iodine to 5.8 parts by mass of magnesium powder and 60 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 123 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3.5 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 53 parts by mass, and the mass of the ether is 70 parts by mass; after cooling to room temperature, add 70 parts by mass of an ether dispersion of a modified flame retardant filler, and complete the addition within 60 minutes, reflux for reaction for 5.5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 10 parts by mass, and the mass of the ether is 60 parts by mass; then add 60 parts by mass of methanol, stir at room temperature for 70 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0056] (2) 101 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2.2, followed by filtration and drying, and then added to dichloromethane (15 times the mass of the composite curing agent) and stirred for 60 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 4 hours, and the dichloromethane was removed by rotary evaporation at 50° C. to obtain a secondary mixture;

[0057] (3) 384 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0058] The preparation steps of the toughening agent are as follows: 16.44 parts by mass of N-p-coumaryltyramine is dissolved in 74 parts by mass of 1,4-dioxane, and then 11.2 parts by mass of isophorone diisocyanate trimer is added at 3s / drop, the temperature is raised to 82°C and stirred for reaction for 4.5h, and then 81.9 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.9 parts by mass of 4-bromophenol is dissolved in 74 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4.5h. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 72°C to obtain a toughening agent.

[0059] The preparation steps of the modified flame retardant filler are as follows: 2.6 parts by mass of dopamine hydrochloride and 7 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethyl)aminomethane-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 35 minutes, the mixture is stirred and reacted at room temperature for 25 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 25 hours to obtain hexagonal boron nitride wrapped with polydopamine; 11 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.6 parts by mass of a silane coupling agent are added, ultrasonicated for 25 minutes, stirred at 500 rpm at 82°C for 6.5 hours, and then centrifuged at 6000 rpm for 10 minutes, washed with ethanol three times, and vacuum dried at 60°C for 25 hours to obtain a modified flame retardant filler.

[0060] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:1.2.

[0061] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.6.

[0062] (Comparative Example 1)

[0063] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0064] 382 parts by mass of epoxy resin, 7.5 parts by mass of modified flame retardant filler, 100.5 parts by mass of composite curing agent, 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed uniformly, and then extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed crusher and passed through a 160-mesh sieve to obtain a flame retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0065] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0066] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:1.

[0067] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0068] (Comparative Example 2)

[0069] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0070] (1) Slowly add 5 parts by mass of a toughening agent and 0.25 parts by mass of iodine to 5.7 parts by mass of magnesium powder and 55 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 112 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 52 parts by mass, and the mass of the ether is 60 parts by mass; after cooling to room temperature, add 57.5 parts by mass of an ether dispersion of a modified flame retardant filler, and complete the addition within 60 minutes, reflux for reaction for 5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 7.5 parts by mass, and the mass of the ether is 50 parts by mass; then add 50 parts by mass of methanol and stir at room temperature for 60 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0071] (2) 100.5 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2, followed by filtration and drying, and then added to dichloromethane (10 times the mass of the composite curing agent) and stirred for 45 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 3 hours, and the dichloromethane was removed by rotary evaporation at 45° C. to obtain a secondary mixture;

[0072] (3) 382 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0073] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0074] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0075] The silane coupling agent is 4-benzonitrileoxybutyltrimethoxysilane.

[0076] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0077] (Comparative Example 3)

[0078] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0079] (1) Slowly add 5 parts by mass of a toughening agent and 0.25 parts by mass of iodine to 5.7 parts by mass of magnesium powder and 55 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 112 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 52 parts by mass, and the mass of the ether is 60 parts by mass; after cooling to room temperature, add 57.5 parts by mass of an ether dispersion of a modified flame retardant filler, and complete the addition within 60 minutes, reflux for reaction for 5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 7.5 parts by mass, and the mass of the ether is 50 parts by mass; then add 50 parts by mass of methanol and stir at room temperature for 60 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0080] (2) 100.5 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2, followed by filtration and drying, and then added to dichloromethane (10 times the mass of the composite curing agent) and stirred for 45 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 3 hours, and the dichloromethane was removed by rotary evaporation at 45° C. to obtain a secondary mixture;

[0081] (3) 382 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0082] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0083] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0084] The silane coupling agent is a mercaptosilane coupling agent.

[0085] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0086] (Comparative Example 4)

[0087] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0088] (1) Slowly add 5 parts by mass of a toughening agent and 0.25 parts by mass of iodine to 5.7 parts by mass of magnesium powder and 55 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 112 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 52 parts by mass, and the mass of the ether is 60 parts by mass; after cooling to room temperature, add 57.5 parts by mass of an ether dispersion of hexagonal boron nitride, and complete the addition within 60 minutes, reflux for reaction for 5 hours, and then cool to room temperature, wherein the mass of the hexagonal boron nitride in the ether dispersion of hexagonal boron nitride is 7.5 parts by mass, and the mass of the ether is 50 parts by mass; then add 50 parts by mass of methanol, stir at room temperature for 60 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0089] (2) 100.5 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2, followed by filtration and drying, and then added to dichloromethane (10 times the mass of the composite curing agent) and stirred for 45 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 3 hours, and the dichloromethane was removed by rotary evaporation at 45° C. to obtain a secondary mixture;

[0090] (3) 382 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0091] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0092] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0093] (Comparative Example 5)

[0094] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0095] (1) Slowly add 5 parts by mass of a toughening agent and 0.25 parts by mass of iodine to 5.7 parts by mass of magnesium powder and 55 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 112 parts by mass of a mixture of a toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 3 hours, wherein the mass of the toughening agent in the mixture of the toughening agent and ether is 52 parts by mass, and the mass of the ether is 60 parts by mass; after cooling to room temperature, add 57.5 parts by mass of an ether dispersion of a modified flame retardant filler, and complete the addition within 60 minutes, reflux for reaction for 5 hours, and then cool to room temperature, wherein the mass of the modified flame retardant filler in the ether dispersion of the modified flame retardant filler is 7.5 parts by mass, and the mass of the ether is 50 parts by mass; then add 50 parts by mass of methanol and stir at room temperature for 60 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix;

[0096] (2) 100.5 parts by weight of the composite curing agent and 36% by weight of hydrochloric acid solution were mixed in a mass ratio of 1:2, followed by filtration and drying, and then added to dichloromethane (10 times the mass of the composite curing agent) and stirred for 45 minutes, and then added to the premix obtained in step (1) and continued to stir and react for 3 hours, and the dichloromethane was removed by rotary evaporation at 45° C. to obtain a secondary mixture;

[0097] (3) 382 parts by mass of epoxy resin, the secondary mixture obtained in step (2), 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed and uniformly extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0098] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0099] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0100] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:1.

[0101] The composite curing agent is 4,4-diaminodiphenylmethane.

[0102] (Comparative Example 6)

[0103] A method for preparing a flame retardant insulating powder coating for new energy vehicles, the preparation steps comprising:

[0104] 382 parts by mass of epoxy resin, 57 parts by mass of toughening agent, 7.5 parts by mass of modified flame retardant filler, 100.5 parts by mass of composite curing agent, 5 parts by mass of leveling agent, 1 part by mass of benzoin, and 0.7 parts by mass of accelerator were manually mixed uniformly, and then melt-mixed and extruded into sheets by a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed crusher and passed through a 160-mesh sieve to obtain a flame retardant insulating powder coating for new energy vehicles; the temperature setting of the extruder was: 85°C in zone I and 100°C in zone II.

[0105] The preparation steps of the toughening agent are as follows: 16.42 parts by mass of N-p-coumaryltyramine are dissolved in 72 parts by mass of 1,4-dioxane, and then 11.1 parts by mass of isophorone diisocyanate trimer is added at 2s / drop, the temperature is raised to 80°C and stirred for reaction for 4 hours, and then 79.85 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.85 parts by mass of 4-bromophenol is dissolved in 72 parts by mass of 1,4-dioxane, and the stirring reaction is continued for 4 hours. After the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 70°C to obtain a toughening agent.

[0106] The preparation steps of the modified flame retardant filler are as follows: 2.4 parts by mass of dopamine hydrochloride and 6 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution with a pH of 8.5, and after ultrasonic treatment for 30 minutes, the mixture is stirred at room temperature for reaction for 24 hours. After the reaction is completed, the mixture is vacuum filtered, and the precipitate is washed with deionized water until the filtrate is colorless, and then dried at 60°C for 24 hours to obtain hexagonal boron nitride wrapped with polydopamine; 10 parts by mass of hexagonal boron nitride wrapped with polydopamine are added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.5 parts by mass of a silane coupling agent are added, ultrasonic treatment is performed for 20 minutes, stirring is performed at 500 rpm at 80°C for 6 hours, and then high-speed centrifugation is performed at 6000 rpm for 10 minutes, washing is performed with ethanol three times, and vacuum drying is performed at 60°C for 24 hours to obtain a modified flame retardant filler.

[0107] The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:1.

[0108] The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.5.

[0109] Effect example

[0110] The flame retardant insulating powder coating for new energy vehicles prepared in the examples and comparative examples was sprayed on the substrate in the form of electrostatic spraying, and then cured in an oven at 200° C. for 15 min to form a film, thereby obtaining a flame retardant insulating coating with a thickness of 150 μm.

[0111] Apparent performance test: The test was conducted according to the method of HG / T 2006-2006 "Thermosetting Powder Coatings", wherein the pinhole situation was observed visually according to Section 5.9. The apparent performance of the flame-retardant insulating coatings prepared in the examples and comparative examples was observed.

[0112] Impact resistance test: referring to GB / T 1732-2020 Determination of impact resistance of paint film, a paint film impactor was used to carry out forward and recoil performance tests on the flame-retardant insulating coatings prepared in the embodiments and comparative examples. The cured sample plate was placed flat on the base of the impactor, and a 1 kg weight was used to drop freely from a certain height to perform forward or recoil impact on the coating. After the test, the sample plate was taken out and a magnifying glass was used to observe whether there were cracks, wrinkles and peeling at the impact point.

[0113] Bending test: refer to GB / T 30791—2014 T-bend test for paints and varnishes to test the T-bend of the flame-retardant insulating coatings prepared in the examples and comparative examples.

[0114] Flame retardancy test: The flame retardant insulating powder coatings for new energy vehicles prepared in the examples and comparative examples were tested according to the "UL94 Flame Retardancy Test Method and Standard", wherein V0 means that the coating does not burn with high temperature or open flame.

[0115] Corrosion resistance: According to GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes, the flame retardant insulating coatings prepared in the embodiments and comparative examples were tested using a salt spray tester; a cross was made on the test sample plate with a knife, the test sample plate was scratched to the bottom plate and placed in a salt spray box, and a salt spray test was carried out with a sodium chloride solution for 500 h, and the rust was peeled off to measure the corrosion length.

[0116] Insulation performance: Refer to "GB / T 1408.1-2016 Test method for electrical strength of insulating materials" and use a voltage breakdown tester to test whether the flame retardant insulating coating meets the breakdown voltage requirement of ≥5kV.

[0117] Self-repairing performance: The flame-retardant insulating powder coatings for new energy vehicles prepared in the embodiments and comparative examples were prepared into standard specimens according to "GB / T1040.1-2018 Determination of tensile properties of plastics Part 1: General Principles", and their original tensile strength was tested by a tensile testing machine. Then, a crack with a depth of 2 mm and a length of 10 mm was cut in the middle of the unstretched original specimen, and the specimen was placed in a mold and kept warm at a humidity of 70% and a temperature of 80°C for 24 hours to observe whether the specimen is repaired.

[0118] Table 1 below shows the performance test results of the flame retardant insulating powder coatings and flame retardant insulating coatings for new energy vehicles prepared in the examples and comparative examples:

[0119] Table 1

[0120] Surface performance Impact strength / cm T-bend Corrosion length / mm Flame retardant Insulation properties Self-healing performance Example 1 Smooth, bright and delicate Positive and negative stroke 60 1T 0.19 V0 The breakdown voltage meets the requirements Rip Repair Example 2 Smooth, bright and delicate Positive and negative stroke 65 1T 0.16 V0 The breakdown voltage meets the requirements Rip Repair Example 3 Smooth, bright and delicate Positive and negative stroke 65 1T 0.18 V0 The breakdown voltage meets the requirements Rip Repair Comparative Example 1 There are pinholes on the coating surface Positive and negative stroke 55 2T 0.18 V0 The breakdown voltage meets the requirements Rip Repair Comparative Example 2 Smooth, bright and delicate Positive and negative stroke 55 1T 0.19 V0 The breakdown voltage meets the requirements The rift has not been repaired Comparative Example 3 There are pinholes on the coating surface Positive and negative stroke 55 1T 0.17 V0 The breakdown voltage meets the requirements Rip Repair Comparative Example 4 There are pinholes on the coating surface Frontal charge 50 failed 3T 0.51 V1 The breakdown voltage meets the requirements The rift has not been repaired Comparative Example 5 Smooth, bright and delicate Positive and negative stroke 55 2T 0.28 V1 The breakdown voltage meets the requirements The rift has not been repaired Comparative Example 6 There are pinholes on the coating surface Positive and negative stroke 60 2T 0.17 V0 The breakdown voltage meets the requirements Rip Repair

[0121] It can be seen from Table 1 that by comparing Examples 1 to 3 with Comparative Examples 1 to 6, the flame retardant insulating powder coatings for new energy vehicles prepared in Examples 1 to 3 have good flame retardancy, insulating properties, corrosion resistance, toughness, impact resistance, and surface properties, and have self-repairing properties.

[0122] The difference between Comparative Example 1 and Example 2 is that the flame-retardant insulating powder coating for new energy vehicles in Comparative Example 1 does not add a toughening agent, and directly mixes the epoxy resin, modified flame-retardant filler, composite curing agent, leveling agent, benzoin, and accelerator, thereby omitting the premix preparation of step (1) and the secondary mixture treatment of step (2) in Example 2, and it is impossible to form a benzophenone imine derivative in the flame-retardant insulating powder coating for new energy vehicles. Compared with Comparative Example 1, the flame-retardant insulating powder coating of Example 2 has better toughness, impact resistance, and surface performance.

[0123] The difference between Comparative Example 2 and Example 2 is that the silane coupling agent of the modified flame retardant filler in Comparative Example 2 does not use mercaptosilane coupling agent but only uses 4-benzonitrileoxybutyltrimethoxysilane. Compared with Comparative Example 1, the flame retardant insulating powder coating for new energy vehicles in Example 2 has better impact resistance and self-repairing performance.

[0124] The difference between Comparative Example 3 and Example 2 is that the silane coupling agent of the modified flame retardant filler in Comparative Example 3 does not use 4-benzonitrileoxybutyltrimethoxysilane, but only uses a mercaptosilane coupling agent, and no benzophenone imine derivatives can be formed in the flame retardant insulating powder coating for new energy vehicles. Compared with Comparative Example 3, the flame retardant insulating powder coating for new energy vehicles of Example 2 has better apparent performance and impact resistance.

[0125] The difference between Comparative Example 4 and Example 2 is that Comparative Example 4 directly uses the ether dispersion of hexagonal boron nitride to prepare the flame-retardant insulating powder coating for new energy vehicles, and no benzophenone imine derivatives can be formed in the flame-retardant insulating powder coating for new energy vehicles. Compared with Comparative Example 4, the flame-retardant insulating powder coating for new energy vehicles of Example 2 has better toughness, impact resistance, surface performance and flame retardancy, and has self-repairing properties.

[0126] The difference between Comparative Example 5 and Example 2 is that the curing agent of Comparative Example 5 only uses 4,4-diaminodiphenylmethane. Compared with Comparative Example 5 and Example 2, the flame retardant insulating powder coating for new energy vehicles has better flame retardancy, corrosion resistance, toughness, impact resistance, and surface performance, and has self-repairing properties.

[0127] The difference between Comparative Example 6 and Example 2 is that when preparing the flame-retardant insulating powder coating for new energy vehicles in Comparative Example 6, the raw material components are directly mixed and melted and extruded; dibenzophenone imine derivatives cannot be formed during the preparation process, and the apparent performance of the flame-retardant insulating powder coating for new energy vehicles in Example 2 is better than that in Comparative Example 6.

[0128] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A flame retardant insulating powder coating for new energy vehicles, characterized in that: The raw material components include, by weight: 380-384 parts by weight of epoxy resin, 56-58 parts by weight of toughening agent, 5-10 parts by weight of modified flame retardant filler, 100-101 parts by weight of composite curing agent, 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator; The toughening agent is obtained by reacting isophorone diisocyanate trimer, 4-bromophenol and N-p-coumaryl tyramine; The modified flame retardant filler is obtained by first wrapping hexagonal boron nitride with polydopamine and then modifying it with a silane coupling agent; The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent; The composite curing agent includes 4,4-diaminodiphenylmethane and amino-mercapto-functional organopolysiloxane; The flame-retardant insulating powder coating for new energy vehicles is prepared by first reacting a toughening agent and magnesium in anhydrous ether, introducing iodine to initiate the reaction during the reaction, then adding a modified flame-retardant filler for a premixing reaction, then adding methanol for alcoholysis to obtain a premix, then remixing the premix with a composite curing agent, and finally melt-mixing and extruding the premix with an epoxy resin, a leveling agent, benzoin, and an accelerator.

2. A method for preparing a flame retardant insulating powder coating for new energy vehicles as claimed in claim 1, characterized in that: The preparation steps include: (1) Slowly add 5 parts by mass of toughening agent and 0.24 to 0.26 parts by mass of iodine to 5.6 to 5.8 parts by mass of magnesium powder and 50 to 60 parts by mass of anhydrous ether under stirring, then heat to a slightly boiling state, and dropwise add 101 to 123 parts by mass of a mixture of toughening agent and ether under a slightly boiling state, and complete the dropwise addition within 60 minutes, and then reflux for 2.5 to 3.5 hours, wherein the mass of toughening agent in the mixture of toughening agent and ether is 51 to 53 parts by mass, and the mass of ether is 50 to 70 parts by mass. After cooling to room temperature, add 45-70 parts by mass of ether dispersion of modified flame retardant filler, add within 60 minutes, reflux for 4.5-5.5 hours and then cool to room temperature, wherein the mass of modified flame retardant filler in the ether dispersion of modified flame retardant filler is 5-10 parts by mass, and the mass of ether is 40-60 parts by mass; then add 40-60 parts by mass of methanol, stir at room temperature for 50-70 minutes, filter, and dry overnight at 70°C under nitrogen protection to obtain a premix; (2) 100-101 parts by weight of the composite curing agent and 36% hydrochloric acid solution are mixed in a mass ratio of 1:1.8-2.2, followed by filtration and drying, followed by adding 5-15 times the mass of the composite curing agent into dichloromethane and stirring for 30-60 minutes, followed by adding the premix obtained in step (1) and continuing to stir and react for 2-4 hours, and removing dichloromethane by rotary evaporation at 40-50° C. to obtain a secondary mixture; (3) 380-384 parts by weight of epoxy resin, the secondary mixture obtained in step (2), 5 parts by weight of leveling agent, 1 part by weight of benzoin, and 0.7 parts by weight of accelerator were manually mixed and then extruded into sheets by melt mixing using a twin-screw extruder at a speed of 35 rpm. After the sheets were cooled, they were ground in a high-speed pulverizer and passed through a 160-mesh sieve to obtain a flame-retardant insulating powder coating for new energy vehicles.

3. The method for preparing the flame retardant insulating powder coating for new energy vehicles according to claim 2, characterized in that: The preparation steps of the toughening agent are as follows: 16.4-16.44 parts by mass of N-p-coumaryltyramine is dissolved in 70-74 parts by mass of 1,4-dioxane, then 11-11.2 parts by mass of isophorone diisocyanate trimer is added at 1-3s / drop, the temperature is raised to 78-82°C and stirred for reaction for 3.5-4.5h, and then 77.8-81.9 parts by mass of a mixed solution of 4-bromophenol is added, wherein 7.8-7.9 parts by mass of 4-bromophenol is dissolved in 70-74 parts by mass of 1,4-dioxane, the stirring reaction is continued for 3.5-4.5h, and after the reaction is completed, the solvent 1,4-dioxane is removed by rotary evaporation at 68-72°C to obtain the toughening agent.

4. The method for preparing the flame retardant insulating powder coating for new energy vehicles according to claim 2, characterized in that: The preparation steps of the modified flame retardant filler are as follows: 2.2-2.6 parts by mass of dopamine hydrochloride and 5-7 parts by mass of hexagonal boron nitride are added to 1000 parts by mass of 10 mmol / L, pH 8.5 tris(hydroxymethylaminomethane)-hydrochloric acid buffer solution, ultrasonically treated for 25-35 minutes, stirred at room temperature for reaction for 23-25 ​​hours, vacuum filtered after the reaction, washed the precipitate with deionized water until the filtrate was colorless, and then dried at 60°C for 23-25 ​​hours to obtain polydopamine-wrapped hexagonal boron nitride; 9-11 parts by weight of hexagonal boron nitride wrapped with polydopamine were added to an ethanol aqueous solution with a volume ratio of 49:1, and then 0.4-0.6 parts by weight of a silane coupling agent were added, ultrasonicated for 15-25 minutes, stirred at 500 rpm for 5.5-6.5 hours at 78-82°C, and then centrifuged at 6000 rpm for 10 minutes, washed with ethanol for multiple times, and vacuum dried at 60°C for 23-25 ​​hours to obtain a modified flame retardant filler.

5. The method for preparing the flame retardant insulating powder coating for new energy vehicles according to claim 4, characterized in that: The silane coupling agent is obtained by combining 4-benzonitrileoxybutyltrimethoxysilane and mercaptosilane coupling agent in a mass ratio of 1:0.8-1.

2.

6. The method for preparing the flame retardant insulating powder coating for new energy vehicles according to claim 2, characterized in that: The composite curing agent is obtained by combining 4,4-diaminodiphenylmethane and amino-mercapto functional organic polysiloxane in a mass ratio of 1:0.4-0.6.

Citation Information

Patent Citations

  • Heatproof anti-corrosion high-flame-retardant epoxy resin powder paint

    CN105315846A

  • Curable compositions

    CN105431476A

  • Organic silicon and fluoride epoxy resin powder coating with ultraviolet resistance and corrosion resistance

    CN108546495A

  • Corrosion-resistant pipeline coating material and preparation method thereof

    CN118852951A

  • Flame-retarding polyurethane foam

    JP1990166112A

Cited By

  • Scratch-resistant flame-retardant insulating powder coating, preparation method thereof and application of scratch-resistant flame-retardant insulating powder coating in rail transit and new energy automobiles

    CN121022256A

  • Heat-conducting nylon plastic and preparation method thereof

    CN121628360A

  • Low-temperature fast curing coating for new energy automobile and energy storage and preparation method of low-temperature fast curing coating

    CN121652687A